The Effect of Language Congruency on the Out‐of‐Hospital Management of Chest Pain. Issue 2 (2nd July 2013) - Sterling, Madeline R.; Echeverria, Sandra E.; Merlin, Mark A.
Abstract: Language incongruences between patients and providers are associated with delays in hospital based care, yet little is known about how they affect the prehospital setting. The out‐of hospital (OOH) management of chest pain is protocol driven, however communication likely influences care provided by paramedics of Emergency Medical Services (EMS) units. This is a cross‐sectional analysis of New Jersey patients who called 911 for chest pain from 2008 to 2011. Using an electronic record system, we examined the association between language congruency and total on‐scene‐time (OST) spent by advanced life support (ALS) paramedics. A series of linear regression models were built to examine this association. Eleven thousand two hundred forty‐nine patients with chest pain were included in our study. Of these, 222 had language incongruences with paramedics (1.98%). Contrary to expectations, language incongruences were associated with less OST (β = 0 − 0.85400, p < 0.0028). After adjusting for demographic and clinical variables, language incongruences persisted as a significant independent predictor of less OST. Paramedics spent less time with Hispanics (β = − 0.3717, p < 0.0228) and Asians (β = −0.5647, p < 0.0101). The association between language incongruences and OST varied significantly among racial/ethnic groups in adjusted models. Language incongruences between patients and paramedics are associated with decreased OST suggesting that disparities may not occur in the prehospital setting .